2021
DOI: 10.1029/2021gl094977
|View full text |Cite
|
Sign up to set email alerts
|

Arctic Amplification of Precipitation Changes—The Energy Hypothesis

Abstract: Arctic precipitation increases can freshen the Arctic Ocean surface and reduce sea ice loss, and affect the mass balance of high-latitude glaciers and ice sheets (Bintanja et al., 2018;Bintanja & Selten, 2014;Min et al., 2008). Understanding what drives increased precipitation sensitivity to climate change in the Arctic is fundamental to build confidence in future projections of Arctic precipitation change and narrow their spread.Arctic amplification of both temperature and humidity changes is strongest during… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 37 publications
1
23
0
Order By: Relevance
“…However, this explanation does not seem plausible for CanESM2 and GFDL-CM3 because their SIAs are the smallest among the six SMILEs (Figure S4d in Supporting Information S1). Pithan and Jung (2021) proposed energy-constraint and moisture-constraint mechanisms driving Arctic precipitation change (see their Figure 4). Accordingly, we speculate that these mechanisms in the models may be not simulated well, leading to discrepancies in the seasonal shifts of precipitation.…”
Section: Discussion and Concluding Remarksmentioning
confidence: 99%
“…However, this explanation does not seem plausible for CanESM2 and GFDL-CM3 because their SIAs are the smallest among the six SMILEs (Figure S4d in Supporting Information S1). Pithan and Jung (2021) proposed energy-constraint and moisture-constraint mechanisms driving Arctic precipitation change (see their Figure 4). Accordingly, we speculate that these mechanisms in the models may be not simulated well, leading to discrepancies in the seasonal shifts of precipitation.…”
Section: Discussion and Concluding Remarksmentioning
confidence: 99%
“…Indeed, studies have shown that this Siberian pathway is gaining importance in recent decades (Komatsu et al, 2018;Mewes and Jacobi, 2019). To explain this, several studies have linked the marked retreat of sea ice in the Barents Sea to enhanced local evaporation, moistening, and cyclone-associated precipitation (e.g., Rinke et al, 2019;Crawford et al, 2022), while Pithan and Jung (2021) have questioned the role of local sea-ice changes for the atmospheric moisture budget.…”
Section: Meridional Energy Transportmentioning
confidence: 99%
“…However, despite the extensive amount of research on the polar amplification of temperature change, there are other aspects of the climate system that also exhibit polar-amplified changes in response to elevated greenhouse-gas concentrations. For example, under warming, the relative change in precipitation is also predicted to be largest in the polar regions, where a substantial absolute increase in precipitation coincides with small precipitation rates in the present-day climate (Bengtsson et al 2011, Bintanja and Selten 2014, Bintanja and Andry 2017, McCrystall et al 2021, Pithan and Jung 2021.…”
Section: Introductionmentioning
confidence: 99%
“…The polar amplification of precipitation change has largely been attributed to an increase in poleward moisture transport (Bengtsson et al 2011) and surface evaporation related to sea ice retreat Selten 2014, Kopec et al 2016). However, more recent work that examined GCMs without sea ice loss has challenged this perspective and instead argued that precipitation change in the Arctic is mainly related to local radiative cooling changes that balance latent heat release from precipitation (Pithan and Jung 2021). Yet the exact processes that cause changes in radiative cooling remains unclear, and how these processes influence model projections of precipitation change has not been examined in detail.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation